2004
DOI: 10.1159/000079483
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of S-1, a Novel Oral Fluorouracil Antitumor Drug, for a Chronic Renal Failure Patient Maintained on Hemodialysis

Abstract: Objective: S-1 is a novel oral fluorouracil antitumor drug that combines three pharmacological agents: tegafur (FT), a prodrug of 5-fluorouracil (5-FU); 5-chloro-2,4-dihydroxypyridine (CDHP), an inhibitor of dihydropyrimidine dehydrogenase, and potassium oxonate (Oxo), a reducer of gastrointestinal toxicity. S-1 has safe and potent antitumor effects in patients with gastric cancer via these respective functions. However, the plasma 5-FU concentration is suspected to accumulate in patients with renal dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…As we reported previously, the overall response rate (complete response + partial response) to S‐1–IFN is 17%, and the response rate among patients with lung metastases is 21% 9 . With regard to drug metabolism, 53.7% of CDHP, an inhibitor of dihydropyrimidine dehydrogenase, is excreted into the urine, 11 and thus S‐1 promotes high plasma concentrations of 5‐FU in hemodialysis patients 14,15 . In this regard, the safety of S‐1 is yet to be ascertained in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As we reported previously, the overall response rate (complete response + partial response) to S‐1–IFN is 17%, and the response rate among patients with lung metastases is 21% 9 . With regard to drug metabolism, 53.7% of CDHP, an inhibitor of dihydropyrimidine dehydrogenase, is excreted into the urine, 11 and thus S‐1 promotes high plasma concentrations of 5‐FU in hemodialysis patients 14,15 . In this regard, the safety of S‐1 is yet to be ascertained in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 66%
“…9 With regard to drug metabolism, 53.7% of CDHP, an inhibitor of dihydropyrimidine dehydrogenase, is excreted into the urine, 11 and thus S-1 promotes high plasma concentrations of 5-FU in hemodialysis patients. 14,15 In this regard, the safety of S-1 is yet to be ascertained in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, several studies have reported that adjusting S-1 doses based on the results of pharmacokinetics studies improves the safety and efficacy of treatment for advanced gastric cancer, even in maintenance for HD patients with chronic renal failure. 15,21,22 As for UFT, a previous report indicated that although the plasma 5-fluorouracil concentrations of HD patients treated with UFT were approximately double those seen in patients with normal renal function, no severe adverse reactions occurred in any of these patients. 23 The optimal doses of chemotherapy drugs for HD patients are uncertain, because there are few previous case reports about the use of chemotherapy to treat HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first-line regimen in Japan for advanced and unresectable gastric cancer is S-1/cisplatin combined chemotherapy, for which safety and efficacy have been characterized in the SPIRITS trial [2] . Nevertheless, both drugs are known to be nephrotoxic and should not be administered to renal failure patients [6] . Recently, oxaliplatin has been used to treat gastric cancer in Japan based on the results of the CLASSIC trial [7] .…”
Section: Discussionmentioning
confidence: 99%